An investigation of the activity of α/β-Hydrolase domain-containing 6 (ABHD6) in rat brain - Alatawi, Abdullah (2025)
The endocannabinoid system plays a role in various physiological processes, with 2-arachidonoylglycerol (2-AG) and anandamide (AEA) as key signalling molecules. Within this system α/β-Hydrolase Domain-Containing 6 (ABHD6) and α/β-Hydrolase Domain-Containing 12 (ABHD12) regulate 2-AG hydrolysis while also metabolizing other endogenous lipid substrates. ABHD6 hydrolyzes multiple lipid classes, including lysophospholipids, bis(monoacylglycero)phosphate (BMP), and diacylglycerol (DAG), while ABHD12 plays a central role in the metabolism of lysophosphatidylserine (Lyso-PS). Given their involvement in diverse lipid signaling pathways, this thesis aims to investigate the activity of ABHD6 in rat brain tissue using a recently developed spectrophotometric assay based on 4-methylumbelliferylheptanoate (4-MUH) hydrolysis and to validate the selectivity and potency of ABHD6 and ABHD12 inhibitors through the Activity-Based Protein Profiling (ABPP) technique.